(untitled) (Bangladesh Journal of Zoology, 2016)
This study was conducted in Merbok estuary, Kedah, Malaysia during January to December 2011 to assess monthly and seasonal variation in food items in the stomach of Chelon subviridis and Valamugil buchanani. A total of 341 fish samples (225 for Chelon subviridis and 116 for Valamugil buchanani) were collected from upper zone (Lalang and Sameling Rivers) of Merbok estuary. Among the stomach contents plant materials, diatom, cyanobacteria and detritus were the main food items in both fish species. In both fishes the highest numbers of food items were found in the month of November. Chelon subviridis consumed plant materials 65.84% by number and 8.55% by frequency of occurrence in the dry season whereas 66.25% by number and 9.73% by frequency of occurrence in the wet season. On the other hand, Valamugil buchanani consumed plant materials 59.54% by number and 12.28% by frequency of occurrence in the dry season whereas 72.89% by number and 11.96% by frequency of occurrence in the wet season respectively. Monthly variations of diatom as food item between C. subviridis and V. buchanani were found to be statistically significant (p<0.05). Both of the fish species consumed more food (by numerical method) in wet season than dry season. Bangladesh J. Zool. 43(2): 213-220, 2015